Author Correction: Intestinal microbiome adjusts the innate immune setpoint during colonization through negative regulation of MyD88 - Bjørn E. V. Koch (Nature Portfolio, 2019)
The original version of this Article contained an error in the spelling of the author Shuxin Yang, which was incorrectly given as Shuxing Yang. This has now been corrected in both the PDF and HTML versions of the Article.